Method Comparison for Bone Density in Multiple Myeloma Patients - Nohel, Michal; Mézl, Martin; Válek, Vlastimil; Dostál, Marek; Chmelík, Jiří (Czech Society for Biomedical Engineering and Medical Informatics, 2024)
Bone mineral density (BMD) is an important indicator of bone health, particularly in patients with conditions such as multiple myeloma. This study aims to compare three methodologies for quantifying BMD in vertebral regions affected by lytic lesions: two using data from conventional CT with different corrections for tissue composition, and one using data acquired on a dual-energy CT system. Method 1 is based on conventional CT with corrections using reference values for muscle and fat, Method 2 uses conventional CT with corrections based on the measured CT values of paraspinal muscle, and Method 3 is based on dual-energy CT. The Wilcoxon signed-rank test was used for statistical comparison, as the dataset did not follow a normal distribution. The results indicated significant differences between Methods 1 and 2 for BMD in regions of interest (ROIs) within lytic lesions, while no significant differences were found for other comparisons in this group. For vertebrae affected by multiple myeloma, significant differences were found between Methods 1 and 2, and Methods 2 and 3, but not between Methods 1 and 3. In healthy vertebrae, a significant difference was found only between Methods 2 and 3. When all ROIs were combined, significant differences were found between Methods 1 and 2, and Methods 2 and 3, with no difference between Methods 1 and 3. Future research will focus on objectively assessing the accuracy of these methods by comparing their results with a calibration phantom.

Bone mineral density (BMD) is an important indicator of bone health, particularly in patients with conditions such as multiple myeloma. This study aims to compare three methodologies for quantifying BMD in vertebral regions affected by lytic lesions: two using data from conventional CT with different corrections for tissue composition, and one using data acquired on a dual-energy CT system. Method 1 is based on conventional CT with corrections using reference values for muscle and fat, Method 2 uses conventional CT with corrections based on the measured CT values of paraspinal muscle, and Method 3 is based on dual-energy CT. The Wilcoxon signed-rank test was used for statistical comparison, as the dataset did not follow a normal distribution. The results indicated significant differences between Methods 1 and 2 for BMD in regions of interest (ROIs) within lytic lesions, while no significant differences were found for other comparisons in this group. For vertebrae affected by multiple myeloma, significant differences were found between Methods 1 and 2, and Methods 2 and 3, but not between Methods 1 and 3. In healthy vertebrae, a significant difference was found only between Methods 2 and 3. When all ROIs were combined, significant differences were found between Methods 1 and 2, and Methods 2 and 3, with no difference between Methods 1 and 3. Future research will focus on objectively assessing the accuracy of these methods by comparing their results with a calibration phantom.
Method Comparison for Bone Density in Multiple Myeloma Patients
Keywords: Spine; bone mineral density; BMD; Multiple myeloma; spectral CT; Spine; bone mineral density; BMD; Multiple myeloma; spectral CT